Mechanical characteristics of asynchronous hyromotor at minimum time for its acceleration and limitation of current - Повстень, В. А.; Макаров, И. Е.; Аузеллаг, Д. (Proceedings of National Aviation University (archive), 1998)
Obtained is general analytical ratio determining maximum possible values of electromagnetic moment the asynchronous short-circuited motor can develop in the process of acceleration at given current limitation and amplitude-frequency starting control. Given are regulatory changes of modern hyrodevices with asynchronous motor and other dependences and data